PENDIDIKAN KETERAMPILAN PENGUSAHA KULINER - Mujiono Mujiono; Sofino Sofino; Ilham Abdullah (Jurnal Pendidikan Sepanjang Hayat, 2020)
The purpose of this study is to describe the success of the Solo 99 super meatball culinary business in the city of Bengkulu, as many as three subjects in this study. This research is a qualitative research. Data collection techniques using interview, observation and documentation. Data analysis techniques include data reduction, data presentation and conclusion drawing. Checking the validity of the data using triangulation techniques. The research results show that first, there is a form of success obtained during running a meatball culinary business in the form of assets such as shop houses, boarding houses, cars and motorcycles as well as gaining popularity and benefits of building an economic system in the vicinity. Second, the acquisition of meatballs culinary entrepreneurship skills education is obtained by the owner by self-taught by learning from experience, actively asking and paying attention and diligently reading books and looking for info from social media. Third, the effort to develop innovative businesses is to make new innovations in food and beverage menus and the process of making meatball balls so that they can be promoted. Fourth, the obstacle faced is the price of raw materials going up and down or unstable. Fifth, the solution made to deal with existing problems is by reducing the portion of meatballs that are sold but not too much. Keywords: Success, Business, Culinary, Meatballs